microRNAs are Stable in Formalin-Fixed Paraffin-Embedded Archival Tissue Specimens of Colorectal Cancers Stored for up to 28 Years - Bovell, Liselle (2012)
MicroRNAs (miRNAs) have prognostic and therapeutic value for colorectal cancers (CRCs). Although formalin-fixed paraffin-embedded (FFPE) tissues are available for biomarker studies, the stability of miRNAs in these tissues stored for long periods (>20 years) is unknown. The present effort involved analysis of 345 FFPE CRC tissues, stored for 6 to 28 years (1982-2004), for the expression of six miRNAs (miR-20a, miR-21, miR-106a, miR-181b, miR-203, and miR-324-5p) using TaqMan® microRNA assays and quantitative real-time PCR (qRT-PCR). Evaluation, by linear regression analysis, of miRNA expression among archived CRC tissues found similar levels of all six miRNAs in tissues stored over this period (correlation coefficients, R(2), ranged from <0.0001-0.009; and t-test p-values were ≥ 0.05). Thus, miRNAs are stable in FFPE tissues stored for long periods of time, and such samples can be used for discovery of biomarkers.